Energy-Aware Cloud Computing Simulators: A State of the Art Survey - Ammara SAJJAD; Aleena Aqdus KHAN; Muhammad Aleem (International Journal of Applied Methods in Electronics and Computers, 2018)
Cloud computing is an emerging technology that offers pay-per-use IT services around the world. The daily increase in Cloud infrastructures and modern IT demands (such as web applications, scientific, and business) results in large-scale data centers that lead to additional electricity consumption. The high energy consumption causes a high operating cost and involves a large amount of carbon dioxide emissions that are harmful to the atmosphere. Many academic, governmental, and industrial studies show that energy consumed by computers and different communication units in a data center plays a significant role in the increase of data center operating costs. It is difficult to calculate the performance, security problems, and energy consumption in a true Cloud computing infrastructure. Therefore, in recent years, several simulation tools have been introduced to help researchers for the analysis of a Cloud computing environment. Cloud simulators need to perform simulation tests to reduce the various complexities in Cloud computing environments. Some Cloud simulators have been specially created to test the performance of Cloud computing environments. This study presents the comparative analysis of the state-of-the-art energy aware Cloud simulators. For comparison, several characteristics, functions, and models are employed for most famous energy aware Cloud simulators such as Green Cloud, CloudSim, iCanCloud, Cloud Analyst, Network CloudSim, and CloudReport.